Rembrandt and the Loneliness of Christ: Osip Mandelstam’s *** [Like Rembrandt, Martyr of Chiaroscuro…] and Aleksander Wat’s The Gospel also as a Literary Masterpiece - Śniedziewska, Magdalena (Porównania, 2021)
In this article, I try to describe the relationships (that have been overlooked by researchers) between texts and characters appearing on Rembrandt’s canvases. I am interested in the relationship between the poem by Mandelstam *** [Like Rembrandt, martyr of chiaroscuro…], the essay of Wat Gospel also as a masterpiece of literature and Rembrandt’s image of Christ and – importantly in the case of Wat – the Batavian chieftain, Claudius Civilis. Examples of works by Mandelstam and Wat show that Rembrandt’s painting can be used not only to express personal fears, but also allows to organize the relationship between the human entity and history: thus it becomes not only an aesthetic but also an existential challenge. I also prove that the work of Mandelstam and Wat, so strongly connected with the tragic fate of these poets, found its culmination in their deaths.